CIVIL PROTECTION MODERN ASPECTS IN CASE OF DISASTERS - BULGARIA - Nikolina Radeva; Maria Panteleeva; Hristianna Romanova (Peytchinski Publishing, 2016)
This article aims on the modern aspects of Civil Protection in Bulgaria by thorough research of the management and the organization of its activities. We used descriptive analysis and summary of scientific publications and state documents concerning the nature, goals, objectives, principles and remedies available to the population in disasters. A study of the documents on the establishment and development of civil protection in Bulgaria was made. In Bulgaria the organization of the civil protection in disasters includes actions on prevention, emergency rescue, relief and recovery. The structure of the main Integrated Rescue System components was built throughout the country in accordance with the administrative - territorial division, each of which supports 24-hour readiness to respond. The basic principles for protection and prevention should be known by all the citizens because they give the right for defense for each person and priority of the human life rescue. The conclusion is that the Bulgarian Civil Protection aspects are up to date and correspond to the modern principles of protection, applied in other European Union Мember states.